Development of E-Module For Chemistry Based on Bengkulu's Local Wisdom To Improve Student Learning Outcomes - Yunitasari, Yunitasari; April Yanti, Fitri; Danim, Sudarwan; Putra, Syalendra (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this research is to develop a chemistry e-module based on local wisdom in Bengkulu using Canva and Flip PDF Professional. It also aims to determine the effectiveness, efficiency, and practicality of e-modules as well as the degree to which they raise students' chemistry learning outcomes. A module based on customs from the Bengkulu people. The ADDIE development stages analysis, design, development, implementation, and evaluation are used in this study's use of the Research and Development technique at MAN 2 Bengkulu City. Questionnaires and assessments of learning outcomes are two methods used to collect data. Following the use of the e-module, student learning outcomes were 80.59, with an 88.24% completion rate. The t test findings show that the e-module is beneficial in enhancing learning outcomes; for alpha = 5%, the t count of 15.52 is greater than the t table of 1.694. The average student assessment for the product efficiency component of the chemistry e-module was 3.5, falling into the good category with an 87.5% percentage, according to the results of the student questionnaire. In contrast, the average student evaluation for the product's usefulness factor was 3.53, placing it in the good category with an 88.25% percentage